ANTI-Candida activity of ethanolic extract of Libidibia ferrea (Research, Society and Development, 2021)
Candidiasis among the fungal infections that affect humans presents, with Candida albicans as the most common etiologic agent, however Candida parapsilosis and Candida tropicalis have emerged as causes of candidiasis episodes. Native to the Brazilian Atlantic Forest, a Libidibia ferrea, is a plant that has been studied for its microbiological control capacity. The present work aims to evaluate an antifungal activity of L. ferrea on C. parapsilosis, C. albicans and C. tropicalis. The evaluation of the antifungal capacity of the ethanolic extracts of L. ferrea was done using the method of serial macrodilution, and inhibition was identified in the maximum concentration tested, from 1.3% of the extract yield, according to the sensitivity test in plates. The antifungal capacity will be assessed using the broth dilution test and the diffusion disc method. In addition, an analysis of the synergism between the extract and antifungals traditionally used will be carried out. Thus, it is expected that the ethanolic extract of L. ferrea will inhibit the growth of Candida ssp cells, thus generating a candidate for antifungal in association with conventional treatment or in monotherapy.